Synthesis of nitrogen-substituted pyran-2-ones via radical cyclisation approach - Mohd Nor, Siti Mariam; Mohd Fauzi, Nawwar Fathiah; Ismail, Intan Safinar (Contemporary Research Center, Australia, 2013)
Four new4-N-substituted pyran-2-ones (δ-lactones) were successfully synthesised from their corresponding cyanoalcohols via two reaction steps; (i) acylation and (ii) radical cyclisation. Four cyanobromoesters that were produced from acylation were treated with tris(trimethylsilyl)silane (TTMSH) and azobisisobutyronitrile (AIBN) in toluene to obtain 5-hydro-4-imino-3,6- dimethylpyran-2-one (4a), 4-amino-5-hydro-3,6,6-trimethylpyran-2-one (4b),3,5-dihydro-4-imino- 6-methylpyran-2-one (4c), and 3,5-Dihydro-4-imino-6,6-dimethylpyran-2-one (4d).